The interaction effect of organizational and individual factors on knowledge sharing behavior: The case of Kazakhstan / Sanat Kozhakhmet - Sanat , Kozhakhmet (2019)
One of the key challenges for contemporary organizations is finding methods of motivating employees to share their knowledge and expertise with their peers. A number of firms try to deal with this challenge by implementing different knowledge management systems. However, despite investments in knowledge management systems, knowledge sharing often does not simply occur. Research findings report that a significant reason for this is that individuals are often reluctant or uneager to share their personal knowledge. Consequently, it is important to understand the factors that might influence employees’ behavior in this arena. Previous studies have attempted to understand knowledge sharing behavior from different perspectives; however, only a few of them have pursued both an organizational and a psychological perspective on how knowledge sharing behavior is instigated. The aim of this study is to fill that gap by investigating how investment in employee development and psychological capital influence knowledge sharing behavior. In addition, this research seeks to explore how organizational identification moderates the investment in employee development-psychological capital and psychological capital-knowledge sharing behavior links. From a critical review of the literature, a research model was proposed to address the answers to the research questions. Data was collected through questionnaires completed by 240 employees of large companies operating in Kazakhstan, and Partial Least Squares Path Modeling was used to analyze the data. The research findings support four out of the six hypotheses. The results revealed that the influence of investment in employee development on knowledge sharing behavior was mediated by psychological capital. Moreover, it was found that organizational identification moderates the relationship between employees’ psychological capital and knowledge sharing behavior. However, the same variable did not modify the relationship between investment in employee development and psychological capital. The results of this research can help companies by allowing them to better understand how to foster knowledge sharing behavior in a more effective way. In addition, the study provides theoretical and practical contributions to knowledge management studies.